Pemanfaatan media Sosial instagram Dalam Pemasaran UMKM Roti Al Batsit Kota Bengkulu - Susena, Karona Cahya; Refsi, Refsi Roziana (Universitas Dehasen Bengkulu, 2023)
UMKM Roti Al Batsit is a small business engaged in the food industry which is located in the city of Bengkulu. As one of the MSMEs, the challenge that must be faced is how to increase product sales and introduce the Roti Al Batsit brand to the public. Therefore, a community service program with the title